In search of a growth model for Italy: the failed attempt of an export-led recovery strategy? - Alessandro Bramucci (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2024)
We analyse Italy's growth pattern from 2001 to 2019 using the demand and growth regime categories proposed in the post-Keynesian tradition and recently adopted in the comparative political economy (CPE) literature. We argue that after the Global Financial and Economic Crisis (GFEC), Italy followed an export-led recovery strategy. In this respect, Germany's growth model emerged as the successful model to follow. In the dominant view, Germany's economic success since the mid-2000s was attributed to a series of painful but necessary economic reforms. The success of Germany's export-led mercantilist regime became particularly attractive to Italy given the similar export-oriented manufacturing industry. However, Italy has followed the 'wrong' German model based on wage compression and restrictive budget policies while the 'true' German model is based on non-price competitiveness factors.
Keywords: E10; E69; F14; 330; demand and growth regimes; export-led growth; competitiveness; internal devaluation; Germany; Italy